Improved Science Learning Outcomes of Relationship Between Ecosystem Components through Audio Visual Media - Dhessriyatno Fajar Nugroho (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve student learning outcomes on the material relations between components of ecosystems and food webs. This research is a classroom action research (PTK) which is conducted in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fifth grade students of SD Negeri Kaliwiru Semarang in the 2020/2021 school year, totaling 24 students. Data collection techniques, data presentation, and drawing conclusions. Research shows that the application of audio-visual learning media can improve student learning outcomes on the material on the relationship between ecosystem components and food webs in class V SD Negeri Kaliwiru in the 2020/2021 academic year as evidenced by the percentage of learning outcomes in cycle I of 37.5% , in cycle II amounted to 91.5% and cycle III 95.8%.